Developing of applications on the Googles Android powered devices and Arduino-powered platforms 1 - Muhammad Syafiq Ma'arof (2015)
Smartphone have taken a pivotal role in the current society that many found impossible to do without. Smartphones have increasing become more sophisticated in its features while still remaining affordable. As such, smartphone are now capable of replacing many devices with similar features like directional bank ATMs, iPods and roadmaps. [28]